Ecological Barriers for an Amphibian Pathogen: A Narrow Ecological Niche for Batrachochytrium salamandrivorans in an Asian Chytrid Hotspot - Dan Sun; Gajaba Ellepola; Jayampathi Herath; Madhava Meegaskumbura (Journal of Fungi, 2023)
The chytrid fungal pathogens Batrachochytrium salamandrivorans (Bsal) and B. dendrobatidis (Bd) are driving amphibian extinctions and population declines worldwide. As their origins are believed to be in East/Southeast Asia, this region is crucial for understanding their ecology. However, Bsal screening is relatively limited in this region, particularly in hotspots where Bd lineage diversity is high. To address this gap, we conducted an extensive Bsal screening involving 1101 individuals from 36 amphibian species, spanning 17 natural locations and four captive facilities in the biodiversity-rich Guangxi Zhuang Autonomous Region (GAR). Our PCR assays yielded unexpected results, revealing the complete absence of Bsal in all tested samples including 51 individuals with Bd presence. To understand the potential distribution of Bsal, we created niche models, utilizing existing occurrence records from both Asia and Europe. These models estimated potential suitable habitats for Bsal largely in the northern and southwestern parts of the GAR. Although Bsal was absent in our samples, the niche models identified 10 study sites as being potentially suitable for this pathogen. Interestingly, out of these 10 sites, Bd was detected at 8. This suggests that Bsal and Bd could possibly co-exist in these habitats, if Bsal were present. Several factors seem to influence the distribution of Bsal in Asia, including variations in temperature, local caudate species diversity, elevation, and human population density. However, it is climate-related factors that hold the greatest significance, accounting for a notable 60% contribution. The models propose that the specific climatic conditions of arid regions, primarily seen in the GAR, play a major role in the distribution of Bsal. Considering the increased pathogenicity of Bsal at stable and cooler temperatures (10–15 °C), species-dependent variations, and the potential for seasonal Bd-Bsal interactions, we emphasize the importance of periodic monitoring for Bsal within its projected range in the GAR. Our study provides deeper insights into Bsal’s ecological niche and the knowledge generated will facilitate conservation efforts in amphibian populations devastated by chytrid pathogens across other regions of the world.